Powder for dust cores and dust cores

Coating soft magnetic powder with niobium alkoxide and forming an insulating layer addresses hysteresis and eddy current losses in powder magnetic cores, enhancing energy efficiency and reducing heat generation.

JP7603630B2Active Publication Date: 2024-12-20TAMURA KK
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2022044995
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-03-22
Publication Date
2024-12-20
Estimated Expiration
2042-03-22

AI Technical Summary

Technical Problem

Existing powder magnetic cores face challenges in reducing hysteresis and eddy current losses, which are critical for improving energy efficiency and reducing heat generation in diverse applications such as office automation equipment and solar power generation systems.

Method used

A powder for powder magnetic cores is developed by coating soft magnetic powder with niobium alkoxide, which forms niobium oxide on the surface, and is then covered with an insulating layer, followed by a heat treatment and pressure molding to create a powder magnetic core.

Benefits of technology

The solution effectively reduces hysteresis and eddy current losses, leading to lower iron loss and improved magnetic properties, maintaining core density and quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007603630000003
    Figure 0007603630000003
  • Figure 0007603630000004
    Figure 0007603630000004
  • Figure 0007603630000005
    Figure 0007603630000005
Patent Text Reader

Abstract

To provide a dust core powder and a dust core, capable of reducing hysteresis loss and eddy current loss, thereby reducing iron loss.SOLUTION: Dust core powder includes soft magnetic powder and niobium alkoxide adhering to the surface of the soft magnetic powder. The niobium alkoxide preferably adheres to the soft magnetic powder at a ratio of 0.10 wt.% or more and 2.00 wt.% or less, and more preferably adheres to the soft magnetic powder at a ratio of 0.50 wt.% or more and 1.00 wt.% or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a powder for dust cores and a dust core containing the powder for dust cores. [Background technology]

[0002] Coil components such as reactors are used in a variety of applications, including office equipment, solar power generation systems, and automobiles. Coil components have a coil attached to a core. Powder magnetic cores are often used for this core.

[0003] A dust core is made of a powder for dust cores. Specifically, the powder for dust cores includes soft magnetic powder and an insulating layer formed around the soft magnetic powder, and the soft magnetic powder with the insulating layer formed thereon is compressed under high pressure of several tons to several tens of tons to produce a dust compact. The dust core is then produced by subjecting the dust compact to a heat treatment called annealing.

[0004] Due to requirements for improved energy exchange efficiency and low heat generation, powder magnetic cores are required to have magnetic properties that minimize energy loss when magnetic flux density changes. The magnetic property related to energy loss is specifically iron loss (Pcv). Iron loss (Pcv) is expressed as the sum of hysteresis loss (Ph) and eddy current loss (Pe). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 5929819 [Patent Document 2] JP 2017-098426 A Summary of the Invention [Problem to be solved by the invention]

[0006] Research has been conducted to reduce hysteresis loss or eddy current loss and reduce iron loss. For example, as in Patent Document 1, research has been conducted to reduce hysteresis loss when the powder particle size or crystal grains are coarse. In addition, as in Patent Document 2, research has been conducted to reduce eddy current loss by separating the core and the coil by a certain distance or more. However, in recent years, the applications of coil components have become more diverse, and there is an even greater demand for reducing hysteresis loss and eddy current loss, i.e., reducing iron loss.

[0007] The present invention has been made to solve the above problems, and an object of the present invention is to provide a powder for dust cores and a dust core that can reduce hysteresis loss and eddy current loss and can reduce iron loss. [Means for solving the problem]

[0008] In order to achieve the above object, the powder for dust core of the present invention comprises a soft magnetic powder, and a niobium alkoxide attached to the surface of the end. The niobium alkoxide is attached so as to cover the entire surface of the particles of the soft magnetic powder or the aggregates of the particles. It is characterized by the fact that

[0009] A powder magnetic core containing the powder for powder magnetic cores is also an aspect of the present invention. 、 Niobium oxide formed by oxidizing niobium alkoxide adheres to the surface of the soft magnetic powder. The niobium oxide is attached so as to cover the entire surface of the particles of the soft magnetic powder or the aggregates of the particles. It may be possible. Effect of the Invention

[0010] According to the present invention, it is possible to obtain a powder for dust cores and a dust core that can reduce hysteresis loss and eddy current loss and can reduce iron loss. [Brief description of the drawings]

[0011] [Figure 1] 1 is a graph showing the relationship between the amount of niobium alkoxide added and core loss. [Diagram 2]1 is a graph showing the relationship between the amount of niobium alkoxide added and hysteresis loss. [Diagram 3] 1 is a graph showing the relationship between the amount of niobium alkoxide added and eddy current loss. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] (Embodiment) The powder for dust core and the dust core according to the present embodiment will be described in detail below. Note that the present invention is not limited to the embodiment described below.

[0013] Powder cores are magnetic materials used in the cores of coil components installed in office equipment, solar power generation systems, automobiles, etc. Powder cores are made by compressing powder for powder cores and annealing it. Powder for powder cores includes soft magnetic powder. Powder for powder cores is made by attaching niobium alkoxide to the surface of this soft magnetic powder. In addition, the soft magnetic powder with niobium alkoxide attached is covered with an insulating layer. The soft magnetic powder covered with this insulating layer is pressure-molded to make a powder compact, and this powder compact is annealed to make a powder core.

[0014] The soft magnetic powder is mainly composed of iron. Examples of the soft magnetic powder include pure iron powder, permalloy (Fe-Ni alloy) mainly composed of iron, Si-containing iron alloy (Fe-Si alloy), sendust alloy (Fe-Si-Al alloy), and a mixture of two or more of these powders. The soft magnetic powder may be an amorphous alloy or a nanocrystalline alloy powder.

[0015] The pure iron powder contains 99% or more Fe. When using permalloy (Fe-Ni alloy), the ratio of Fe to Ni is preferably 50:50 or 25:75, but other ratios are also acceptable. For example, Fe-80Ni or Fe-36Ni may be used. In addition to Fe and Ni, Si, Cr, Mo, Cu, Nb, Ta, etc. may be contained. The Si-containing iron alloy may contain Co, Al, Cr, or Mn.

[0016] Examples of the Fe-Si alloy powder include Fe-3.5%Si alloy powder and Fe-5.5%Si alloy powder, but the ratio of Si to Fe may be other than 3.5% or 5.5%. The Fe-Si-Al alloy is a ternary alloy made of iron, silicon, and aluminum, and contains, for example, about 6 wt% to 10 wt% Si and about 4 wt% to 5 wt% Al relative to Fe, but may also contain about 1 wt% to 3 wt% Ni relative to Fe, and may further contain Co, Cr, or Mn.

[0017] This soft magnetic powder may be produced by a pulverization method or an atomization method. In the pulverization method, a lump of soft magnetic powder is mechanically pulverized. If the lump of soft magnetic powder is large, it is pulverized by a jaw crusher, a hammer mill, a stamp mill, or the like, and if the lump of soft magnetic powder is small, it is pulverized by a ball mill, a vibration mill, or the like. In addition, the atomization method may be any of a water atomization method, a gas atomization method, and a water gas atomization method. For example, in the gas atomization method, gas is blown onto soft magnetic powder melted at high temperature to pulverize it, and then it is cooled and solidified.

[0018] The soft magnetic powder preferably has a median diameter D50 in the particle size distribution of 20 μm or less. Because niobium alkoxide is liquid, it is possible to uniformly disperse niobium alkoxide even in soft magnetic powder with a small particle size of 20 μm or less.

[0019] It is preferable to carry out a powder heat treatment process in which the soft magnetic powder is heat-treated before the niobium alkoxide is attached. By carrying out this powder heat treatment process, the soft magnetic powder becomes easier to disintegrate and easier to classify into the desired particle size. The powder heat treatment is carried out by heating for about 2 hours in a non-oxidizing atmosphere such as nitrogen gas, hydrogen gas, a mixed gas of nitrogen and hydrogen, or a low-oxygen atmosphere with an oxygen concentration of about 0.01%, or in the air. The heat treatment temperature is preferably 500°C or higher and 900°C or lower.

[0020] Niobium alkoxide is attached to the surface of the soft magnetic powder. This niobium alkoxide may be attached to the surface of each particle of the soft magnetic powder, or may be attached to the surface of a particle aggregate, or both of these modes may be mixed. In addition, the niobium alkoxide may be attached so as to cover the entire surface of the particle or particle aggregate, or may be attached so as to cover a part of the surface of the particle or particle aggregate.

[0021] Niobium alkoxides are represented by the general formula Nb(OR)5, where R in the formula is the same or different alkyl group, and the number of carbon atoms of the alkyl group is 1 or more. Examples of niobium alkoxides include pentaethoxyniobium represented by the chemical formula Nb(OC2H5)5, where all alkyl groups have 2 carbon atoms. Other examples include penta-n-propoxyniobium represented by the chemical formula Nb(On-C3H7)5, penta-n-butoxyniobium represented by the chemical formula Nb(On-C4H9)5, and penta-sec-butoxyniobium represented by the chemical formula Nb(o-sec-C4H9)5.

[0022] Although this is a conjecture and the mechanism is not limited to this, it is speculated that the niobium attached to the surface of the soft magnetic powder repairs lattice defects in the crystals of the soft magnetic powder, thereby reducing hysteresis loss. It is also speculated that the niobium alkoxide attached to the surface of the soft magnetic powder is heat-treated and oxidized in the process of making the powder core, thereby acting as an insulating layer and reducing eddy current loss.

[0023] Although the amount of niobium alkoxide added is small, it has the effect of reducing hysteresis loss and eddy current loss, and is preferably 0.10wt% to 2.00wt% relative to the soft magnetic powder, and more preferably 0.50wt% to 1.00wt% relative to the soft magnetic powder. At 0.10wt% to 2.00wt%, the effect of reducing hysteresis loss and eddy current loss is significant, and as a result, iron loss can be reduced. At 0.5wt% to 1.00wt%, the effect of reducing hysteresis loss is more significant, and the effect of reducing loss is also large. Mixing can be performed using a planetary mixer with rotating blades in a container, a high-speed stirring granulator, or the like.

[0024] After the niobium alkoxide is added, heat treatment is performed in a nitrogen atmosphere. The heat treatment temperature is preferably 350° C. or higher and 800° C. or lower. The heat treatment time is about 2 hours at the peak temperature, but may be changed appropriately depending on the heat treatment temperature.

[0025] After the niobium alkoxide is attached to the soft magnetic powder, an insulating layer formed of an insulating resin is formed on the soft magnetic powder in an insulating layer forming step. When the niobium alkoxide is attached so as to cover the entire surface of the particles or particle aggregates, the insulating layer is formed on the surface of the niobium alkoxide, and when the niobium alkoxide is attached so as to cover only a portion of the surface of the particles or particle aggregates, a portion of the insulating layer is also formed on the surface of the soft magnetic powder.

[0026] The insulating material constituting the insulating layer includes a silane compound, a silicone oligomer, a silicone resin, or a mixture thereof. The insulating layer may be a single layer or multiple layers. For example, the insulating layer may be composed of multiple layers divided by type, or may be a single layer of one type or a mixture of two or more types of insulating materials.

[0027] The silane compound includes a silane compound without a functional group and a silane coupling agent. As the silane compound without a functional group, for example, an alkoxysilane such as an ethoxy type or a methoxy type can be used, and tetraethoxysilane is particularly preferred. As the silane coupling agent, an aminosilane type, an epoxysilane type, or an isocyanurate type silane coupling agent can be used, and 3-aminopropyltriethoxysilane, 3-glycidoxypropyltrimethoxysilane, or tris-(3-trimethoxysilylpropyl)isocyanurate is particularly preferred.

[0028] The amount of the silane compound added is preferably 0.05 wt% or more and 1.0 wt% or less of the soft magnetic powder. By setting the amount of the silane compound added in this range, the fluidity of the soft magnetic powder can be improved, and the density, magnetic properties, and strength properties of the compacted powder core can be improved.

[0029] As the silicone oligomer, methyl-based or methylphenyl-based ones having an alkoxysilyl group and no reactive functional group, epoxy-based, epoxymethyl-based, mercapto-based, mercaptomethyl-based, acrylic methyl-based, methacrylic methyl-based, vinylphenyl-based ones having an alkoxysilyl group and a reactive functional group, or alicyclic epoxy-based ones having a reactive functional group instead of an alkoxysilyl group, etc. can be used. In particular, by using a methyl-based or methylphenyl-based silicone oligomer, a thick and hard insulating layer can be formed. In addition, in consideration of the ease of forming the insulating layer, a methyl-based or methylphenyl-based one having a relatively low viscosity may be used.

[0030] The amount of silicone oligomer added is preferably 0.1 wt% or more and 2.0 wt% or less of the soft magnetic powder. If the amount added is less than 0.1 wt%, it will not function as an insulating layer, and eddy current loss will increase, resulting in reduced magnetic properties. If the amount added is more than 2.0 wt%, it will result in a decrease in the density of the powder magnetic core.

[0031] Silicone resin is a resin that has a siloxane bond (Si-O-Si) as its main skeleton. By using silicone resin, it is possible to form a coating with excellent flexibility. Silicone resin can be methyl-based, methylphenyl-based, propylphenyl-based, epoxy resin-modified, alkyd resin-modified, polyester resin-modified, rubber-based, etc. Among these, when using methylphenyl-based silicone resin in particular, it is possible to form an insulating layer with little loss on heating and excellent heat resistance.

[0032] The amount of silicone resin added is preferably 0.6wt% or more and 2.5wt% or less relative to the soft magnetic powder. If the amount added is less than 0.6wt%, it will not function as an insulating layer, and eddy current loss will increase, resulting in reduced magnetic properties. If the amount added is more than 2.5wt%, it will result in a decrease in the density of the powder magnetic core. More preferably, the amount added is 0.8wt% or more and 2.0wt% or less.

[0033] In this insulating layer forming process, insulating resin is added to the soft magnetic powder, mixed, and then heated and dried. By heating and drying the insulating resin, an insulating layer is formed on the surface of the soft magnetic powder to which the niobium alkoxide is attached. Heat drying conditions are not limited to the above, but the temperature is 70°C or higher and 300°C or lower. If the temperature is lower than 70°C, the formation of the insulating layer may be incomplete, and eddy current loss may increase. On the other hand, if the temperature is higher than 300°C, the binder may not function properly, and the density and magnetic permeability of the powder compact may deteriorate. The heating and drying time is about 2 hours.

[0034] A lubricant is added to the soft magnetic powder around which the insulating layer is formed, and then the powder core is manufactured through a pressure molding process and an annealing process. Examples of the lubricant include stearic acid and its metal salts, as well as ethylene bis stearamide, ethylene bis stearamide, and ethylene bis stearamide. By adding the lubricant, the release pressure when releasing the die is reduced, and the soft magnetic powder is prevented from sticking to the die, improving the quality of the green compact. The amount of the lubricant added is preferably about 0.2 wt% to 0.6 wt% with respect to the soft magnetic powder. By setting the amount within this range, the sliding between the soft magnetic powder particles can be improved. The lubricant may be applied to the inner surface of the die into which the soft magnetic powder is filled in the pressure molding process described later, instead of being added to the soft magnetic powder. The lubricant may also be applied to the inner surface of the die after adding the lubricant to the soft magnetic powder.

[0035] The pressure molding process is a process for producing a green compact by pressure molding the soft magnetic powder on which the insulating layer has been formed. First, the soft magnetic powder is filled into a die, and then, a pressure of 10 to 20 ton / cm is applied. 2 The mixture is pressed at a pressure of 1000 psi to form a green compact.

[0036] In the annealing process, the powder compact produced through the pressure molding process is annealed to remove distortion in the soft magnetic powder. In the annealing process, the powder compact is heat-treated in a non-oxidizing atmosphere such as nitrogen gas, hydrogen gas, a mixture of nitrogen and hydrogen, or a low-oxygen atmosphere of about 0.01%, at a temperature of 650°C or higher, preferably 800°C or higher, and lower than the temperature at which the insulating layer formed around the soft magnetic powder is destroyed (for example, 900°C). By undergoing this annealing process, a powder magnetic core is produced.

[0037] In this way, the powder for the dust core is produced from the soft magnetic powder, and the dust core is produced from the powder for the dust core. When the production of the dust core is completed, the niobium alkoxide may be in the form of niobium oxide and adhered to the soft magnetic powder, or may be in the form of niobium doped into the soft magnetic powder.

[0038] (Example) The present invention will be described in more detail with reference to examples, but the present invention is not limited to the following examples.

[0039] Powders for dust cores of Examples 1 to 7 and Comparative Example were prepared as follows, and dust cores were prepared using these powders for dust cores. Examples 1 to 7 and Comparative Example were different only in the amount of niobium alkoxide added, and the other production steps and conditions were the same.

[0040] First, Fe-Si alloy powder was used as the soft magnetic powder. This Fe-Si alloy powder contains 5.5 wt% Si. The Fe-Si alloy powder was heated in a nitrogen atmosphere at 650°C for 2 hours. The Fe-Si alloy powder was heat-treated and crushed, and then sieved to use the Fe-Si alloy powder with a D50 of 20 μm or less in the particle size distribution.

[0041] The particle size, circularity and coercive force of the Fe-Si alloy powder used here are shown in Table 1 below. The particle size and circularity were calculated from 3000 samples using a particle image analyzer (Malvern, device name: morphologi G3S). The Fe-Si alloy powder was dispersed on a glass substrate, the powder was photographed with a microscope, and each sample was automatically measured from the image. The coercive force was measured with an HC meter (Tohoku Steel Co., Ltd., K-HC1000).

[0042] [Table 1]

[0043] Niobium alkoxide was attached to the Fe-Si alloy powder. The niobium alkoxide used was pentaethoxyniobium, which is represented by the chemical formula Nb(OC2H5)5. Pentaethoxyniobium was added to the Fe-Si alloy powder in an amount of 0.00 to 2.50 wt% shown in Table 2 below, including those that were not added (addition amount 0.00 in Table 2), and mixed in a mortar. After adding and mixing pentaethoxyniobium, the Fe-Si alloy powder was heat-treated at 380°C for 2 hours in a nitrogen atmosphere. The 2-hour heat treatment here refers to the time spent at a temperature of 380°C, and this heat treatment took about 10 hours, including the time to heat up to 380°C and the time to lower the temperature.

[0044] After that, 0.5 wt% of silicone oligomer was added to the Fe-Si alloy powder, mixed, and dried at 200°C for 2 hours. After drying, the powder was passed through a sieve with 250 μm openings to eliminate agglomerations. Furthermore, 1.6 wt% of silicone resin (solid content 50%) was added to the sieved Fe-Si alloy powder, mixed, and dried at 150°C for 2 hours to produce a powder for dust cores with an insulating layer formed.

[0045] In order to eliminate aggregation, the Fe-Si alloy powder was passed through a sieve with an opening of 250 μm, and a lubricant (Acrawax (registered trademark)) was added at 0.5 wt%. The Fe-Si alloy powder to which the lubricant was added was filled into a die and subjected to a pressure of 15 ton / cm. 2 The powder compact was then annealed at 850°C for 2 hours in an atmosphere with an oxygen concentration of 0.01%, to produce each powder core.

[0046] The density (g / cm 3 ), initial permeability at 0A / m and permeability at 10kA / m, hysteresis loss (kW / m 3 ), eddy current loss (kW / m 3 ) and iron loss (kW / m 3 ) was measured.

[0047] Density (g / cm 3The outer diameter, inner diameter, and height of the powder core were measured, and the volume (cm) of each compact was calculated from these values. 3 ) into π×(outer diameter 2 -Inner diameter 2 The weight of the powder magnetic core was then measured, and the density was calculated by dividing the measured weight by the calculated volume.

[0048] When measuring each magnetic permeability, 17 turns of φ0.5 mm copper wire were wound around the powder core as the primary winding and 17 turns were wound as the secondary winding. Then, using an LCR meter (Agilent Technologies: 4284A), the initial magnetic permeability and the magnetic permeability at 10 kA / m were calculated from the inductance of the magnetic field strength at 100 kHz and 1.0 V. In addition, using a BH analyzer (Iwatsu Measurement Corporation: SY-8219), a magnetic measuring device, the iron loss Pcv (kW / m 3 ) measurements were carried out.

[0049] Furthermore, from the measurement results of iron loss Pcv, hysteresis loss Ph (kW / m 3 ) and eddy current loss Pe(kW / m 3 ) was calculated. Hysteresis loss Ph (kW / m 3 ) and eddy current loss Pe(kW / m 3 ) was performed by calculating the hysteresis loss coefficient (Kh) and eddy current loss coefficient (Ke) from the frequency curve of iron loss Pcv using the following equations (1) to (3) by the least squares method.

[0050] Pcv = Kh×f + Ke×f 2 (1) Ph = Kh × f (2) Pe = Ke × f 2 (3) Pcv: Iron loss Kh: Hysteresis loss coefficient Ke: Eddy current loss coefficient f: frequency Ph: Hysteresis loss Pe: Eddy current loss

[0051] The measurement results are shown in Table 2. In addition, Fig. 1 is a graph showing the relationship between the amount of niobium alkoxide added and iron loss, Fig. 2 is a graph showing the relationship between the amount of niobium alkoxide added and hysteresis loss, and Fig. 3 is a graph showing the relationship between the amount of niobium alkoxide added and eddy current loss.

[0052] [Table 2]

[0053] As shown in Table 2 and Fig. 1, Examples 1 to 7, in which niobium alkoxide was added, showed a greater reduction in iron loss than the Comparative Example, in which no niobium alkoxide was added. As shown in Fig. 2, the hysteresis loss of Examples 1 to 7 was all reduced compared to the Comparative Example, and in particular, as shown in Fig. 3, the eddy current loss of Comparative Example 1 was 300 (kW / m 3 ), whereas Examples 1 to 7 are close to 70 (kW / m 3 ) and it was confirmed that the eddy current loss was significantly reduced by adding niobium alkoxide.

[0054] It is generally said that increasing the amount of additives reduces the density of a powder magnetic core. However, as shown in Table 2, even in Example 7, which had the largest amount of niobium alkoxide added, the density reduction was only 0.1 (g / cm) compared to the Comparative Example, which did not add niobium alkoxide. 3 ) and no significant decrease was observed.

[0055] In addition, in Examples 2 to 6 in which the amount of niobium alkoxide added was 0.10 wt% or more and 2.00 wt% or less, the iron loss was 850 (kW / m 3 ), and it was confirmed that a lower iron loss was achieved. Furthermore, in Examples 4 and 5, in which the amount of niobium alkoxide added was 0.50 wt% or more and 1.00 wt% or less, the hysteresis loss was 790 (kW / m 3 ), and the iron loss is also below 840 (kW / m 3 ) and it was confirmed that this method has the greatest effect in reducing hysteresis loss and iron loss.

[0056] (Other embodiments) In this specification, an embodiment of the present invention has been described, but this embodiment is presented as an example and is not intended to limit the scope of the invention. The above-mentioned embodiment can be implemented in various other forms, and various omissions, substitutions, and modifications can be made without departing from the scope of the invention. The embodiment and its modifications are included in the scope of the invention and its equivalents described in the claims, as well as in the scope and gist of the invention.

Claims

1. A soft magnetic powder; Niobium alkoxide adhered to the surface of the soft magnetic powder; Equipped with the niobium alkoxide is attached so as to cover the entire surface of the particles of the soft magnetic powder or the aggregates of the particles; A powder for dust cores characterized by:

2. The niobium alkoxide is adhered to the soft magnetic powder in a ratio of 0.10 wt % or more and 2.00 wt % or less. The powder for dust cores according to claim 1 ,

3. The niobium alkoxide is adhered to the soft magnetic powder in a ratio of 0.50 wt % or more and 1.00 wt % or less. The powder for dust core according to claim 1 or 2,

4. The soft magnetic powder has a powder particle size of 20 μm or less in terms of D50 in particle size distribution. The powder for dust cores according to any one of claims 1 to 3, characterized in that

5. The soft magnetic powder is an FeSi alloy powder; The powder for dust cores according to any one of claims 1 to 4, characterized in that

6. The powder for dust core according to any one of claims 1 to 5 is contained. A powder magnetic core characterized by:

7. Niobium oxide formed by oxidizing the niobium alkoxide adheres to the surface of the soft magnetic powder, the niobium oxide is attached so as to cover the entire surface of the particles of the soft magnetic powder or the aggregates of the particles; The powder magnetic core according to claim 6 .

Citation Information

Patent Citations

  • High-temperature sliding material

    JP1984029819A

  • Dust core and soft magnetic metal powder therefor

    JP2007194273A

  • Crystallized glass powder, glass paste, soft magnetic composite material and powder magnetic core

    JP2015105220A

  • Reactor

    JP2017098426A

  • Coil part

    JP2017188588A